PENGARUH LATIHAN PLYOMETRIC UNTUK MENINGKATKAN KEMAMPUAN KOORDINASI TENDANGAN DAN PUKULAN PADA SISWA EKSTRAKULIKULER PENCAK SILAT MAN 3 KOTA PADANG - Tamarotul Jannah; Vega Soniawan; Jeki Haryanto; Kristian Burhan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The problem addressed in this study is the still-low level of kicking and striking coordination. This condition is evident in the suboptimal coordination of movements when performing combinations of kicking and striking techniques. This study aims to determine the effect of plyometric training on kicking and striking coordination abilities among students in the pencak silat extracurricular program at MAN 3 Padang. This study employed a quasi-experimental method using a one-group (pre-test) -(post-test) design. The sample consisted of 10 students selected using purposive sampling. The instrument used was a test of kicking and striking coordination ability. The results showed that the mean (pre-test) score of 34.30 increased to 39.60 on the (post-test) , with a mean difference of 5.30. The results of the hypothesis test using Sig. (2-tailed) = 0.001 < 0.05 indicate that plyometric training has a significant effect on the coordination of kicking and striking skills among students in the pencak silat extracurricular program at MAN 3 Kota Padang.